"A novel mixed-mode current-conveyor-based filter" - Abuelma’atti, M.T. (2004)
A new mixed-mode biquad circuit is presented. The circuit uses six single-output plus-type second-generation current-conveyors (CCII+s), a single dual-output CCII+, two grounded capacitors, eight resistors, at least two of them permanently grounded, and can realize lowpass, highpass, bandpass, notch, lowpass notch, highpass notch and allpass responses from the same topology. The circuit can be driven by voltage or current and its output can be voltage or current. The parameters 0 and 0/Q0 enjoy independent electronic tunability.